1999
DOI: 10.1021/es980833d
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Organic Carbon Normalized Sorption Coefficient (KOC) for Soils Using the Fragment Constant Method

Abstract: A fragment constant model for prediction of K OC was developed and evaluated with a diverse database of 592 chemicals belonging to 17 classes. The range of experimental K OC covered 7.65 log-units. The 592 chemicals were randomly divided into a training set and a testing set for model development and validation. A general model was then established using the entire database having 74 fragment constants and 24 structural factors. Statistically, the regression model accounted for as much as 96.96% of the variati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 23 publications
0
24
0
Order By: Relevance
“…Indeed, in the various models, the same structural aspects, mainly those related to molecular size, are represented by alternative descriptors with a similar meaning for K oc modeling: for instance log K ow , fragments parameters, topological descriptors and MW. Some useful electronic parameters are captured in the different alternative descriptors such as E-state indices [9,30], quantum chemical descriptors (PNSA-1, h[AM1], [AM1], P max ) [32], correction factors [8,27], the number of phenyls, oxygen, nitrogen and sulfur atoms [31] and the number of hydrogen acceptor atoms (nHA, that is the same as using nF plus nO plus nN), the number of nitro groups (nNO), or the maximum positive intrinsic state difference related to the electrophilicity of the molecule (MAXDP) [28].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, in the various models, the same structural aspects, mainly those related to molecular size, are represented by alternative descriptors with a similar meaning for K oc modeling: for instance log K ow , fragments parameters, topological descriptors and MW. Some useful electronic parameters are captured in the different alternative descriptors such as E-state indices [9,30], quantum chemical descriptors (PNSA-1, h[AM1], [AM1], P max ) [32], correction factors [8,27], the number of phenyls, oxygen, nitrogen and sulfur atoms [31] and the number of hydrogen acceptor atoms (nHA, that is the same as using nF plus nO plus nN), the number of nitro groups (nNO), or the maximum positive intrinsic state difference related to the electrophilicity of the molecule (MAXDP) [28].…”
Section: Resultsmentioning
confidence: 99%
“…The experimental data of the soil sorption partition coefficient, normalized on organic carbon (K oc ), of 643 heterogeneous organic compounds were collected from the literature [1,8,9] and compiled into a single database (see Table 1 in supporting information). Some of the chemicals in the literature databases have more than one K oc value, the result of being derived from different sources; in these cases the median was adopted.…”
Section: Experimental Datamentioning
confidence: 99%
See 1 more Smart Citation
“…It was demonstrated that the K oc magnitude for different organic compounds was primarily due to their partition into soil organics [1]. Many linear models have been established, to relate K oc with molecular structures through the methodology of quantitative structureactivity relationships (QSARs), including the models employing molecular connectivity indices (MCI) [2,3], fragment constants [4], characteristic root index (CRI) [5], quantum chemical descriptors [6], etc. To promote the predictivity of log K oc , a general-purpose multilinear regression model (MLR) was developed by Schüürmann et al [7], which is a combination of 24 fragments covering the atoms C, H, N, O, P, S, F, Cl, and Br in various chemical functionalities and 4 molecular descriptors including molecular weight, bond connectivity, molecular E-state, and an indicator for non-polar and weakly polar compounds.…”
Section: Introductionmentioning
confidence: 99%
“…In natural water, sorption and desorption processes affect the fate of hydrophobic organic matters (HOCs) [11][12][13]. Once the PAHs, previously bound to sediments, are released into the aquatic environment, they will act as a natural repository for these HOCs.…”
Section: Introductionmentioning
confidence: 99%